BEBAN KERJA, IMPLIKASINYA TERHADAP MOTIVASI KERJA DENGAN KEMAMPUAN KERJA SEBAGAI VARIABEL INTERVENING PADA KARYAWAN BANK UMKM - Ircham Robbaq Azwar; S Siswanto (Jurnal Keuangan dan Perbankan, 2015)
The purpose of this study was to empirically prove effects of workload veriable to job motivation trough workability as intervening variable. This research is conducted in Bank UMKM Surabaya, East Java. The approach used here is descriptive quantitative with explanatory research method. The sample in this research was 66 respondents and the sampling technique used was probability sampling with simple random sampling approach. In this research, the data was analyzed using validity test, reliability test, T-test, F-test, and path analysis to investigate the direct and indirect effect from workload and workability variables toward the work motivation. From the F-test result, it showed positive and significant from workload and workability variables toward the work motivation, while for the T-test there is no significant effect between workload and work motivation, furthermore there is no significant effect between workload and workability, while between the workability and the work motivation, a positive and significant effect is found. In this case, workload has not directly affected significantly toward work motivation, and workload has indirectly affect the work motivation as the intervening variable.